2022
DOI: 10.20473/jbe.v10i22022.140-150
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Knowledge, Attitude and Practice of Eating Behavior on Stunting and Undernutrition in Children in the Agricultural Area of Jember District, Indonesia

Abstract: Background: Indonesia as an agricultural country is still having nutritional problems (stunting and undernutrition) caused by mothers’ lack of knowledge, attitude and practice of eating behavior. Purpose: This research aims to investigate the impact of knowledge, attitude, and practice of eating behavior of mothers of children under five on stunting and undernutrition prevalence in the agricultural communities in Jember. Methods: This cross-sectional research used questionnaires as a method to collect data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…72 of 2022, stunting is of particular concern in Indonesia and is a target for accelerating the reduction of stunting [16]. Nutrition intervention is one of the programs given to stunting toddlers in the community [17,18]. Researchers in 2021 found that maternal nutrition education and awareness can help reduce rates of stunting and malnutrition in children.…”
Section: Introductionmentioning
confidence: 99%
“…72 of 2022, stunting is of particular concern in Indonesia and is a target for accelerating the reduction of stunting [16]. Nutrition intervention is one of the programs given to stunting toddlers in the community [17,18]. Researchers in 2021 found that maternal nutrition education and awareness can help reduce rates of stunting and malnutrition in children.…”
Section: Introductionmentioning
confidence: 99%